Improving Students’ Writing Ability To Write Procedure Texts Through Group Investigation Method - Doorvina, Doorvina (UNIVERSITAS PAKUAN, 2025)
Procedurei texti isi toi providei informationi toi othersi abouti thei stepsi ori proceduresi ini completingi ai taski ori problem.i However,i thei problemi thati ofteni arisesi isi thati studentsi lacki abilityi ini writing,i includingi ini writingi procedurei text.i Soi iti isi importanti toi improvei students'i abilityi toi writei proceduresi byi usingi thei groupi investigationi method.i Thei researchi objectivesi arei (1)i toi analyzei thei planningi processi ofi Groupi Investigationi methodi ini procedurali texti material,i (2)i toi analyzei thei implementationi processi ofi Groupi Investigationi methodi ini procedurali texti material,i (3)i toi analyzei thei assessmenti ofi thei implementationi ofi Groupi Investigationi methodi ini increasingi students'i writingi abilityi ini procedurali texti materiali ini classi XIi studentsi ofi SMKNi 2i Malinau.i Thei methodi usedi ini thisi researchi isi Classi Actioni Researchi (CAR).i Thei participantsi includedi thei researcheri asi thei Englishi teacheri andi thei eleventhi gradei studentsi ati SMKNi 2i Malinau.i Thei datai collectioni techniquesi usedi ini thisi studyi werei interviews,i observations,i andi testsi conductedi beforei cycle,i cyclei 1,i andi ini cyclei 2.i Thei datai analysisi techniquesi usedi werei qualitativei andi quantitativei analysis. Thei resultsi ofi thisi researchi statei thati studentsi cani improvei theiri procedurali texti writingi skillsi throughi thei groupi investigationi method.i Fromi thei resultsi ofi observations,i studentsi arei morei interestedi andi motivatedi ini learningi toi writei procedurei texts,i andi arei ablei toi writei procedurei textsi correctly.i Fromi thei resultsi ofi thei interviews,i thei responsesi ofi teachersi andi studentsi regardingi thei applicationi ofi thei groupi investigationi methodi werei positivei andi cani bei usedi asi ani effectivei methodi ini teachingi procedurali texts.i Andi fromi thei testi results,i therei wasi ani increasei ini studenti scoresi fromi pre-testi toi post-test..